Bangladeshi nationalism : history of dialectics and dimensions - Osmany, Shireen Hasan (Dhaka, Bangladesh : University Press, 1992)
Includes references to the politics of pre-partition Bengal.
Revision of the author's thesis (Dr. Sc. (Phil.)--Humbolt University, 1990).
Includes bibliographical references (pages [160]-168).
BIED
Keywords: Nationalism -- Bangladesh -- History; Bangladesh -- Politics and government; Bengal (India) -- Politics and government